Bank regulation, risk management, and compliance : theory, practice, and key problem areas - Dill, Alexander, 1953- (Practical finance and banking guides., 2020)
Bank Regulation, Risk Management, and Compliance is a concise yet comprehensive treatment of the primary areas of US banking regulation - micro-prudential, macro-prudential, financial consumer protection, and AML/CFT regulation - and their associated risk management and compliance systems.